PELANGGARAN HAK NORMATIF YANG TERJADI TERHADAP PEMUTUSAN HUBUNGAN KERJA DEWAN DIREKSI - Maria Mulyadi Francisca (Problematika Hukum, 2015)
Rights dispute between the workers and the company completed first bipartite conducted by the Department of Labor. In the event of unilateral termination of the board of directors when the case has not diputusnya Industrial Dispute leads to violations of basic rights. Every employee who works in a company in any position is an employee who has been regulated in employment.Treatment without discrimination to all employees is one manifestation of the welfare of the workforce upheld by the company